One-Step Fabrication of Bioinspired Lubricant-Regenerable Icephobic Slippery Liquid-Infused Porous Surfaces - Zhuo, Yizhi (ACS Omega, 2018)
[Image: see text] Icephobic coating and surfaces are essential for protecting infrastructures such as transmission lines, transportation vehicles, and many others from severe damages of excessive icing. The slippery liquid-infused porous surfaces (SLIPS) are attracting escalating attention because of their low-ice adhesion strength. Despite all of the encouraging laboratory scale results, the SLIPS are still far from being applicable in real environments owing to the key unsolved problem, namely anti-icing durability. Inspired by the functionality of the amphibians’ skin, lubricant regenerability was introduced to conventional SLIPS and realized by a facile and scalable fabrication route. A series of polydimethylsiloxane (PDMS)-based skinlike SLIPS were designed and fabricated by using a one-step method, the solvent evaporation-induced phase separation technique. The obtained skinlike SLIPS were able to regenerate surface lubricant constantly by internal residual stress because of phase separation and survive more than 15 cycles of wiping/regenerating tests. Thanks to the regenerability of the surface lubricant, the new SLIPS demonstrated durable icephobicity, showing a long-term low-ice adhesion strength below 70 kPa, which was only 43% of 160 kPa that for the pristine PDMS (Sylgard 184), even after 15 icing/deicing cycles. This work paves a new and facile way for achieving icephobic durability of SLIPS.